Ordered Macroporous Photonic Crystal Hot Electron Plasmonic Photocatalysts. (8th September 2020) - Collins, Gillian; Lonergan, Alex; McNulty, David; Glynn, Colm; Buckley, Darragh; Hu, Changyu; O'Dwyer, Colm
Abstract : Plasmonic metal-semiconductor heterostructures are promising for photocatalytic applications since the metal and the oxide semiconductor can absorb light in the visible spectrum leading to better catalytic rates. Photon absorption efficiency can be enhanced by fashioning the catalyst into a photonic crystal that can enhance absorption at certain wavelength because of its structure. We show how Au nanoparticle sensitized V2 O5 and TiO2 inverse opal photonic crystals can enhanced reaction rate for catalysis by over an order of magnitude under λ = 532 nm excitation or under white light illumination. This effect is shown to results from spectral overlap of the electronic band gap, localized surface plasmon resonance and the excitation photon energy. When we compare the photocatalytic response of Au-V2 O5 IO with Au-TiO2 IO, we can selectively enhance reaction rates either in the visible or in the UV regions, depending on the bandgap of the semiconductor, and the photonic band gap of the IO. For Au-TiO2 IO, hot electron transfer occurs from the gold into the conduction band, and better catalysis under white light illumination at the TiO2 surface is attributed to improved photon adsorption in the visible by the presence of a photonic band gap, slow light in the photonic crystal to enhance photon absorption, the UV bandgap of the TiO2, and the localised surface plasmon resonance of the Au. For Au-V2 O5, electron transfer to the Au in addition to enhanced absorption in the visible range, promote better catalysis at λ = 532 nm.